The Need for Improved Management of Painful Diabetic Neuropathy in Primary Care - Teresa Sobhy (Pain Research and Management)
The provision of care for patients with type II diabetes in primary care must involve assessing patients for peripheral neuropathy of the feet. Objectives. This paper will demonstrate that painful diabetic neuropathy (PDN) is poorly assessed for and treated in primary care. Methods. A critical analysis of research will be conducted to identify the prevalence and impact of PDN among individuals with type II diabetes. Results. Research evidence and best practice guidelines are widely available in supporting primary care practitioners to better assess for and treat PDN. However, the lack of knowledge, awareness, and implementation of such research and guidelines prevents patients with PDN from receiving appropriate care. Discussion. Much international research exists on the prevalence and impact of PDN in primary care; however, Canadian research is lacking. Furthermore, the quantity and quality of research on treatment modalities for PDN are inadequate. Finally, current research and guidelines on PDN management are inadequately implemented in the clinical setting. Conclusion. The undertreatment of PDN has significant implications on the individual, family, and society. Healthcare practitioners must be more aware of and better implement current research and guidelines into practice to resolve this clinical issue.